(untitled) (Fiep Bulletin - online, 2013)
The development of the motor skills happens starting from the organizing mental functions and managers of the motor behavior. In this context, it is necessary that volleyball athletes improve the mechanisms of identification of the opponent’s actions. Like this, a considered component of great importance in the elaboration, execution and decision of the fast actions made during the game is the metacognition capacity that is directly related to the time of the athlete’s motor reaction. The objective of that research was to verify the relationship of the speed of mental processing with different levels metacognitives, in masculine athletes of volleyball. For so much, a n=15 was used, with age between 18 and 20 years, divided in three groups, in agreement with the individual capacity of metacognition. The five scores superiors characterized the Group Superior Level of Metacognition (GNSM), the five medium scores represented the Group Medium Level of Metacognition (GNMM) and the five scores inferior corresponded to the Group Inferior Level of Metacognition (GNIM). The data were analyzed by ANOVA (Oneway). he/she was differentiates significant in Reaction Discrimination’s Time (TRD). In the post hoc of Tukey it was verified differentiates in the comparison among the groups GNSM-GNIM (p = 0,02). It was ended that the athletes with high level metacognitive were faster in the comparison between groups.